Process research in early intensive intervention in autism spectrum disorder: Sensitivity to change of the autism behavior coding system. Issue 12 (9th August 2019) - Herbrecht, Evelyn; Lazari, Olga; Notter, Marianne; Schmeck, Klaus; Spiegel, René
Abstract : The development of sensitive measures to capture changes in core autism symptoms is crucial in early intervention research. The study examines the sensitivity to change of the Autism Behavior Coding System (ABCS), a video‐based instrument to assess core autism symptoms during therapist‐child interaction. Video sequences of 40 young children treated in the Frühintervention bei Autistischen Störungen center were analyzed with regard to the question of whether short‐term changes during an 18 day period of early intervention could be captured, and whether these results are reflected in an independent clinical assessment (Developmental Disorders‐Child‐Global Assessment Scale [DD‐C‐GAS]). ABCS results showed statistically significant improvements on behavioral domains such as "expression of wishes" and "social cooperative behavior" ( P < 0.01), less pronounced on "eye contact." Improvements on the DD‐C‐GAS were highly significant on all subdomains. Both scales showed high correlations within their subdomains, yet no significant correlations between the changes in both instruments' scores were found. An additional analysis between the DD‐C‐GAS scores at day 18 and the changes in the ABCS scores showed statistically significant associations in the expected direction between the changes in the variable "eye contact" and all DD‐C‐GAS subdomains. The correspondence of the two levels of assessment is low, but the specifics of this relationship deserve further study. The ABCS may prove useful in addition to standard assessment tools, especially in early intervention research settings, as it allows reliable analysis of core behavioral elements in young children with autism. Autism Res 2019, 12: 1817–1828 . © 2019 The Authors. Autism Research published by International Society for Autism Research published by Wiley Periodicals, Inc. Lay Summary: The study examined the sensitivity of an autism‐specific video coding system (ABCS) in assessing changes after an 18 day period of intensive early intervention. Video sequences of therapist‐child‐interaction of 40 young children with autism spectrum disorder (ASD) were analyzed. Children's behavior improved in expression of wishes, social cooperativity and eye contact. A therapist‐based global assessment scale also showed important improvement after 18 days, yet both assessment instruments showed weak correlations between their respective changes. We showed that the ABCS may prove useful in capturing short‐term changes in autism‐related behaviors, especially in early intervention research.